UJI KUALITAS MATERIAL PENYUSUN BEBERAPA PANCI ALUMINIUM BERDASARKAN LAJU KOROSINYA - Khaerunnisa A; Ihsan Ihsan; Hernawati Hernawati (Teknosains, 2014)
Has conducted research entitled "Quality Testing Materials Aluminum Pots Compiler Based on corrosion rate". This study aims to determine the type of material and type of constituent aluminum pan aluminum pot that has good quality based on the corrosion rate. In the community known as rust corrosion. All metal objects both ferrous on ferrous maupucan experience corrosion. Basically, the test can be performed simulative corrosion the laboratory or directly in the field. The solution is used to accelerate the corrosion rate in this study are HCl, HNO3, and NaCl. In testing the corrosion rate used methods of mass reduction, and material composition testing pans were observed by using XRF (X_Ray Florescence). From the test results it is known that the corrosion rate have Java pan corrosion rate faster than the pot Orchid and Eagle brands. While the observation of the authors of each aluminum pan on the market is almost the same, its components such as Al, Fe, Ag, Ga, Nb, Mn, Ni, V, and Hf.